As expectativas e a participação dos pais no processo de desenvolvimento e escolarização do filho diagnosticado com Transtorno de Déficit de Atenção/Hiperatividade - TDA/H. - Silva, Marilete Geralda da (2007)
The present study aimed to understand the relations between the expectations and the forms of participation of the parents in the development and the schooling of the children diagnosed with the Attention Deficit Disorder/ Hyperactivity - ADD/H based on the fact that parents are privileged partners in the education of the children. So for such objective to be reached, a study of four cases of children diagnosed with this disorder (three boys and a girl) and its respective parents was done in the age-group from seven to ten years old when the beginning of the study during the first semester of 2005. For the research of the data collection, guided interviews and participant observations were carried out. The interviews had been carried through with the parents, the children, the professors and pedagogical coordinator of the schools where these children studied at the beginning and in the end of the period of the terms during the semester of each institute. The participant observations happened in the contexts of the house and the school of each child and also in other environments (the sports court, the private teacher´s house, in the course of Mathematics, in the Resource Center, in the presentations of bumba-meu-boi and in the street). The collected data had been organized and categorized from the technique of the content analysis. To the written registers of the participant observations, gathered data of the photographic and phonographic registers were added. These registers were transformed into descriptive texts of the interactions between the citizens of the research. The gathered and organized data were mainly analyzed and interpreted from the psychoanalytical perspective and authors who argue the participation of the parents at school and also the process of pertaining to school inclusion of children with educative special necessities. Taking into consideration the limits of the methodology of this case study, some conclusive inferences related to the applied work were pointed out. They are as follows: the parents have expectations concerning to the development, the schooling and the professionalization of the children, such as the other parents, but they hope the children develop principally good attitudes; the expectations nor always were positive and evidenced to be influenced by the context of the difficulties and easinesses of the children. The participation of the parents has mainly characterized for the search of some professionals to help them in the accompaniment of the children; for the guilt they have concerning to the difficulties of the child; for the monitoring, for the attachment and devotion of the mothers and for the apart participation of the father; and the difficulty in understanding the behavior of the child because of the effects of the medicine regarding the symptoms of the ADD/H. The school attendance is pointed out by the parents as the main factor that helps and makes it difficult the participation in the development and the schooling of the children. The relation between expectations and participation showed: that there is no linearity between them; that not always the participation form is favorable to the reach of the expectations; that expectations and forms of participation point the place that the children occupy in the desire of their parents; that the feelings of the parents related to the children are ambivalent; that a high investment in the participation and the no return of what is waited can generate negative expectations and that not always all participation of the parents is synonymous of help for the child, the school and the proper family. The children perceive that the parents yearn they learn good attitudes and change their behavior; they behave themselves (verbally) in a passive and childish way ahead of the aids that receive; they show good feelings concerning to the classmates and teachers; they also show motivation and independent behavior to carry out their activities at some moments of the study, but they also demonstrate to mobilize some people of the family with their tasks; they have consciousness of the symptoms of the ADD/H that are attributed and show some mistrust of being discriminated for that. Expectations and forms of participation also evidence that the symbolic statute of this disturb is being a great fact, so that the course of the development of these children has already been traced, and it prevents them to make enigmas to their parents. The study also revealed that the attendance excused to the children with ADD/H and their parents at school was not a reflection of inclusion.